Towards a cultural-developmental psychology of music in adolescence. (March 2015) - Miranda, Dave; Blais-Rochette, Camille; Vaugon, Karole; Osman, Muna; Arias-Valenzuela, Melisa
Music is a fundamental cultural product with which adolescents are finely attuned within and across sociocultural contexts. However, very little is known about the intricate interplay among music, psychology, and culture in adolescence. The purpose of this literature review is twofold: (1) to define, ground, and situate a new perspective towards a cultural developmental psychology of music in adolescence; and (2) to find and organize the extant literature pertaining to the cultural and developmental roles of music in adolescence. The rationale is organized in two sections. The first section defines the meaning of a cultural-developmental psychology of music in adolescence. It also explains how this perspective can be grounded in principles of cultural psychology, notably the mutual constitution between culture and the person. It then situates this perspective within established cultural research on music (evolutionary psychology, music perception, and ethnomusicology). The second section presents a critical outlook on the slowly growing but fragmented literature pertaining to culture, psychology, and music in adolescence (music preferences; music motivation and functions; dance; language; social network and multitasking; ethnicity and cultural diversity; and cultural competence in music-based interventions). In conclusion, theoretical and methodological directions are suggested for future cultural research on music in adolescence.